Взаємозалежність здібностей і потреб у розвитку теорії мотивації - Хращевський, Андрій Олексійович (My University, 2013)
Досліджено природу здібностей і потреб, їх взаємозв’язок і співвідношення. Проаналізовано еволюцію взаємодії здібностей і потреб у формуванні сучасної теорії мотивації. The nature of abilities and needs, their interrelation and correlation are investigated. The evolution of the interaction of abilities and needs in the formation of the modern theory of motivation is analyzed.
Keywords: мотивація; motivation; людський потенціал; human potential; здібності людини; human abilities